Webinar Edukasi Kesehatan Warga SDN 3 Nagri Kaler Dalam Menjaga Iman, Imun, Aman Di Era Pandemi COVID-19 - Nova Mira Rizky Wulandari; Lutfi Haidar Ummah; Asri Andriyani Oswita; Khurilyn Jannah; Rima Irfiani; Nurul Ilmi; Nuur Wachid Abdul Majid; Puji Rahayu (Indonesian Journal of Community Services in Engineering & Education (IJOCSEE), 2021)
The educational activities of school people’s health online at the Covid-19 pandemic are to increase understanding and motivate the awareness of SDN 3 Nagri Kaler residents in maintaining faith, immunity, and safety in the era of the COVID-19 pandemic. By media delivery materials of voice notes, videos on software applications, PowerPoint and question, and answer applications through the WhatsApp group platform. It was held on February 13, 2021, presented by Mr. Ihsan Rizali. By looking at the respondents' responses, who are collected over the google form, and the documentation results of the delivery of material, it uses a quantitative descriptive method analysis of the participants' responses. The location of the webinar was held at SDN 3 Nagri Kaler, Purwakarta. The target of this research is all school members in SDN 3 Nagri Kaler. The results of this service show that school members are motivated to maintain faith, immunity, and safety, understand symptoms, treatment, and activities during the COVID-19 pandemic, with 77% of ways to maintain faith, immunity, and safety and 67% of preventive measures.